Atmospheric-Driven and Intrinsic Interannual-to-Decadal Variability in the Kuroshio Extension Jet and Eddy Activities - Nonaka, Masami; Sasaki, Hideharu; Taguchi, Bunmei; Schneider, Niklas (Frontiers in Marine Science, 2020)
To investigate influences of oceanic intrinsic/internal variability and its interannual-to-decadal modulations on the Kuroshio Extension (KE) jet speed and associated eddy activity, a ten-member ensemble integration of an eddy-resolving ocean general circulation model forced by 1965-2016 atmospheric reanalysis is conducted. We found a distinct time-scale dependence in the ratio of forced and intrinsic variability of the KE jet speed. On decadal time scale, the ratio of the magnitude of intrinsic variability to that of atmospheric-driven variability is 0.69, suggesting it is largely atmospheric-driven. In contrast, on interannual time scales, the KE jet speed has large ensemble spread, indicating that it is strongly affected by intrinsic variability and has substantial uncertainty. For eddy activity, ratios of variability in ensemble average and spread also depend on region. In the downstream KE [32°-38°N, 153°-165°E], variability in the ensemble average eddy activity dominates (1.5 times) over rms of its ensemble spread on decadal time scale, and is positively correlated with current speed. Ensemble mean eddy activity in the downstream KE region is correlated (r=0.59) with ensemble mean current speed variability in the central North Pacific 4 years earlier, consistent with westward propagation of wind-driven jet speed anomalies. This linkage is robust even for each ensemble member with the significant lagged correlation also found in seven out of ten ensemble members, suggesting possibility of prediction of the eddy activity. In contrast, eddy activity in the upstream KE [32°-38°N, 141°-153°E] shows very large intrinsic and limited atmospheric-driven variability with a ratio of the former to the latter of 1.96. These results suggest intrinsic variability needs to be considered in interannual variability of strong ocean jet. The dependence of these findings to the model specificities need to be further explored.